Application of an adjusted patient blood management protocol in patients undergoing elective total hip arthroplasty: towards a zero-percent transfusion rate in renal patients—results from an observational cohort study - Hervé Hourlier (BMC, 2021)
Abstract Background Renal patients are at high risk of blood transfusion following major orthopaedic surgery. A variety of patient blood management (PBM) policies have been proposed to reduce the rate of transfusions. The aim of this observational study was to assess the performance of an adjusted PBM protocol in patients with chronic kidney disease (CKD) undergoing elective total hip arthroplasty (THA). Methods A total of 1191 consecutive patients underwent elective unilateral THA and took part in an adjusted PBM protocol. The PBM protocol consisted of epoetin (EPO) alfa therapy prescribed by the surgeon, routine administration of tranexamic acid (TXA), an avascular approach to the hip and postoperative prophylaxis of thromboembolism. The performance of this PBM protocol was analysed in patients with a glomerular filtration rate (GFR) below or above 60 ml/min/1.73 m2 at baseline. Haemoglobin levels were controlled at admission, on postoperative day (POD) 1 and on POD 7 ± 1. A bleeding index (BI) was used as a proxy for blood loss. Results In total, 153 patients (12.9%) presented with a modification of diet in renal disease value below 60 at baseline. Of these, 20 (13.1%) received EPO therapy and 120 (78.4%) received TXA. None of the patients received allogenic blood transfusions during the first perioperative week. The mean BI for the entire study population was 2.7 (95% CI 2.6, 2.8). CKD did not exert a significant impact on the BI (p = 0.287). However, it was found that both TXA and EPO therapy significantly lowered the BI (difference, − 0.3, p < 0.001). There were no thromboembolic complications in renal patients who received TXA and/or EPO therapy. Conclusions A zero-percent transfusion rate during the first perioperative week is attainable in patients with stage 3 or stage 4 CKD undergoing contemporary elective THA. With the use of a pragmatic blood-sparing protocol, patients with renal dysfunction did not have an increased risk of bleeding and did not have an increased incidence in the rate of perioperative blood transfusions.